Intraocular Hemorrhage Causes Retinal Vascular Dysfunction via Plasma Kallikrein - Liu, Jia (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Retinal hemorrhages occur in a variety of sight-threatening conditions including ocular trauma, high altitude retinopathy, and chronic diseases such as diabetic and hypertensive retinopathies. The goal of this study is to investigate the effects of blood in the vitreous on retinal vascular function in rats. METHODS. Intravitreal injections of autologous blood, plasma kallikrein (PK), bradykinin, and collagenase were performed in Sprague-Dawley and Long-Evans rats. Retinal vascular permeability was measured using vitreous fluorophotometry and Evans blue dye permeation. Leukostasis was measured by fluorescein isothiocyanate–coupled concanavalin A lectin and acridine orange labeling. Retinal hemorrhage was examined on retinal flatmounts. Primary cultures of bovine retinal pericytes were cultured in the presence of 25 nM PK for 24 hours. The pericyte-conditioned medium was collected and the collagen proteome was analyzed by tandem mass spectrometry. RESULTS. Intravitreal injection of autologous blood induced retinal vascular permeability and retinal leukostasis, and these responses were ameliorated by PK inhibition. Intravitreal injections of exogenous PK induced retinal vascular permeability, leukostasis, and retinal hemorrhage. Proteomic analyses showed that PK increased collagen degradation in pericyte-conditioned medium and purified type IV collagen. Intravitreal injection of collagenase mimicked PK's effect on retinal hemorrhage. CONCLUSIONS. Intraocular hemorrhage increases retinal vascular permeability and leukostasis, and these responses are mediated, in part, via PK. Intravitreal injections of either PK or collagenase, but not bradykinin, induce retinal hemorrhage in rats. PK exerts collagenase-like activity that may contribute to blood–retinal barrier dysfunction.